More doesn’t mean better: emotion regulation flexibility and subjective well-being in daily life - Wong, Jubilee Changyi (Nanyang Technological University, 2024)
Emotion regulation (ER) flexibility involves the implementation of ER strategies that meet the demands of an emotional situation. While it has been linked to lower psychopathological symptoms and negative affect, its associations with positive affect and short-term cognitive well-being have yet to be established. The paper presents an experience-sampling study that investigates the relationship between one’s variable use of ER strategies across time and situations and three indices of subjective well-being (SWB). Although no significant associations were found between ER flexibility and SWB, this study illuminates the preventative role of ER flexibility on negative psychological outcomes, its role in predicting short-term CWB and the adaptiveness of using a wider versus a smaller range of strategies in ER.